2014
DOI: 10.1177/1477153514524587
|View full text |Cite
|
Sign up to set email alerts
|

Road lighting and pedestrian reassurance after dark: A review

Abstract: This paper concerns road lighting for pedestrians and how this aids reassurance, their confidence when walking alone after dark. Evidence from past studies that lighting enhances reassurance is supported by the findings of an unfocussed approach that aimed deliberately to avoid focus on lighting or fear, thus to counter the unintended potential for focussed, quantitative methods to lead towards such a finding. Review of the characteristics of lighting suggests an optimum illuminance of 10 lux, of high S/P rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 50 publications
1
75
3
Order By: Relevance
“…While this illuminance is at the lower end of current recommendations for lighting in subsidiary roads, 17 suggesting a lower design illuminance could be adopted in some situations, there is also a need to consider the effect of glare and the lighting required for other visual needs of pedestrians such as reassurance 59 and interpersonal judgements 60 which may suggest different characteristics for road lighting. This paper has tended to focus on ablebodied pedestrians: wheelchair users may have different demands.…”
Section: Resultsmentioning
confidence: 99%
“…While this illuminance is at the lower end of current recommendations for lighting in subsidiary roads, 17 suggesting a lower design illuminance could be adopted in some situations, there is also a need to consider the effect of glare and the lighting required for other visual needs of pedestrians such as reassurance 59 and interpersonal judgements 60 which may suggest different characteristics for road lighting. This paper has tended to focus on ablebodied pedestrians: wheelchair users may have different demands.…”
Section: Resultsmentioning
confidence: 99%
“…Further concerns about laboratory studies arise from the fact that test participants know they are being observed which may affect their behaviour 16 and that the level of reassurance 30 does not reflect that experienced in outdoor locations -it is unlikely that confederate pedestrians in the experiments will be considered as threatening, and will thus be allowed to come closer for a given level of comfort. 16 These concerns are addressed in field studies.…”
Section: Studies Of Interpersonal Distancementioning
confidence: 99%
“…"Reassurance" describes the feeling of confidence a pedestrian might gain from road lighting (among other factors) to walk along a road, in particular if walking alone after dark, and is used here to encompass the terms "perceived safety" [Knight 2010] and "fear of crime" [Atkins and others 1991] as used in past studies. Reassurance is that which provides the comfort that makes someone feel less worried or less afraid or doubtful and restores confidence [Fotios, Unwin, and Farrall 2015]. Planning guidance from the UK government identified the need for local development plans to "reassure the public by making crime more difficult to commit .…”
Section: Introductionmentioning
confidence: 99%
“…Using a qualitative approach that aimed to avoid specific focus on lighting, Fotios, Unwin, and Farrall [2015] demonstrated that reassurance is gained by the presence of lighting. This qualitative approach did not permit a statistical analysis of significance but provided parallel support for quantitative investigations that may have unintentionally biased respondents to indicate such an effect; for example, by raising the prominence of lighting among other environmental attributes.…”
Section: Introductionmentioning
confidence: 99%